2018
DOI: 10.32734/idjpcr.v1i1.199
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Troponin and Ck-Mb in Association with Q-Wave Myocardial Infarction

Abstract: Abstract. Acute myocardial infarction (AMI) is the global main cause of morbidity and mortality. AMI describes the process of cell death due to prolonged ischemia identified by the appearance of pathological Q-wave in electrocardiogram (ECG). Myocardial cell death does not occur directly after the onset of myocardial ischemia, however, it occurs more than 6 hours after the onset. Thus, certain cardiac markers, such as cardiac troponin and creatinine kinase-MB (CK-MB) which formed in myocardial cell damage, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A recent analysis of studies in large groups of patients has shown that enzyme release is more common than previously thought and is also associated with prognosis (9)(10)(11). According to findings in essential databases, patients with increased cardiac markers had higher complications and cardiac mortality, independent of other predictors of mortality (12).…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of studies in large groups of patients has shown that enzyme release is more common than previously thought and is also associated with prognosis (9)(10)(11). According to findings in essential databases, patients with increased cardiac markers had higher complications and cardiac mortality, independent of other predictors of mortality (12).…”
Section: Introductionmentioning
confidence: 99%